Modeling and Structure Optimization of Tapped Transformer - Abdelhadi Namoune; Azzedine Hamid; Rachid Taleb (Institute of Advanced Engineering and Science, 2017)
In this paper, a simplified circuit model of the tapped transformer structure has been presented to extract the Geometric and technology parameters and offer better physical understanding. Moreover, the structure of planar transformer has been optimized by using changing the width and space of the primary coil, so as to enlarge the quality factor Q and high coupling coefficient K. To verify the results obtained by using these models, we have compared them with the results obtained by employing the MATLAB simulator. Very good agreement has been recorded for the effective primary inductance value, whereas the effective primary quality factor value has shown a somewhat larger deviation than the inductance.